Node at LinkedIn: The Pursuit of Thinner, Lighter, Faster. - Prasad, Kiran; Norton, Kelly; Coatta, Terry (Communications of the ACM, 2014)
A interview with senior director of mobile engineering at professional networking website LinkedIn, Kiran Prasad, is presented. He discusses LinkedIn's decision to use a JavaScript-based software computing platform, called Node.js, what he finds compelling about Node, and why LinkedIn chose to move away from using the architectural computing pattern, Active Record, of the open source web application framework, Ruby on Rails, as the model representation.